INFUSION THERAPY IN THE PERIOPERATIVE PERIOD IN DOGS AND CATS - Pavlo SOLONIN; Mariia Kulida (Ukrainian Journal of Veterinary Sciences, 2021)
The modern approach to the treatment of animals with surgical pathology requires the application of infusion solutions throughout the whole perioperative period: before the surgery (in case of emergency treatment), during the surgery, and after it. In animals with surgical diseases that come for treatment, there are quite often varying degrees of water-electrolyte balance disorder. The cause of these disorders is both surgical pathology itself (for example, peritonitis, bowel obstruction), and concomitant pathology present in the patient (renal failure, diabetes mellitus, cardiac deficiencies, etc.). The success of surgery treatment largely depends on the proper assessment and correction of these disorders. This article presents modern approaches to the issues on infusion therapy in veterinary surgery of dogs and cats. Great aƩention is paid to the selection of means for infusion therapy in animals in the perioperative period. The article contains examples of determining the volume of solutions for infusion during the preoperative preparation, intensive therapy for massive intraoperative blood loss, and postoperative management of patients